Expression of T-bet, Eomesodermin and GATA-3 in porcine αβ T cells. (July 2016) - Rodríguez-Gómez, Irene M.; Talker, Stephanie C.; Käser, Tobias; Stadler, Maria; Hammer, Sabine E.; Saalmüller, Armin; Gerner, Wilhelm
Abstract: The transcription factors GATA-3, T-bet and Eomesodermin play important roles in T-cell development, differentiation and memory formation. However, their expression has not been studied in great detail in porcine T cells. We report on protein expression at the single cell-level of these transcription factors in thymocytes and mature αβ T cells. GATA-3 expression was found in γδ − thymocytes, with decreasing expression from the CD4 − CD8α − stage towards single-positive stages. Extra-thymic CD4 + T cells but not CD8β + T cells expressed low levels of GATA-3, which decreased with age. CD4 + and CD8β + T-bet + cells mainly displayed a CD8α + CD27 − and perforin + CD27 dim/− phenotype, respectively and had the capacity for IFN-γ production; indicative of an effector/effector memory phenotype. Eomesodermin + αβ T cells had mixed phenotypes in regard to CD8α, CD27 and perforin expression. In conclusion, our data so far support the hitherto reported roles for GATA-3 in T-cell development and T-bet for Th1 effector-differentiation, but question the role of Eomesodermin for memory formation of porcine T-cells. Highlights: Decreasing levels of GATA-3 in thymocytes along the DN-DP-SP maturation pathway. Uniform CD8α + CD27 − phenotype of T-bet + CD4 + T cells. Uniform perforin + CD27 dim/− phenotype of T-bet + CD8β + T cells. Low frequencies of Eomes + CD4 + and CD8β + T cells, partially with naïve phenotype.